IMPLEMENTASI WORKSHOP UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMANFAATKAN KOMPUTER PADA PROSES PEMBELAJARAN DI SMP NEGERI 1 KUBU KABUPATEN ROKAN HILIR - Karsono Karsono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
School action research (SAR) aims to improve the learning system at schools. The purpose of this research was to improve teachers’ ability to utilize computers in teaching through the implementation of workshops. Data in this research were collected through observations and reflections on the actions of teachers at SMP Negeri 1 Kubu in two cycles. The subjects in this study were 20 teachers at SMP Negeri 1 Kubu. The results showed that the implementation of workshops to improve the teachers’ ability to utilize computers in teaching increased with the percentage of 90% (an excellent category). Based on these results, it could be concluded that implementing workshops was effective to improve the teachers’ ability to utilize computers in teaching at SMP Negeri 1 Kubu Babussalam Rokan Hilir Regency.